Characterization of spherical domains at the polystyrene thin film–water interface - Ahmad, Khurshid; Zhao, Xuezeng; Pan, Yunlu; Hussain, Danish (Beilstein Journal of Nanotechnology, 2016)
Spherical domains that readily form at the polystyrene (PS)–water interface were studied and characterized using atomic force microscopy (AFM). The study showed that these domains have similar characteristics to micro- and nanobubbles, such as a spherical shape, smaller contact angle, low line tension, and they exhibit phase contrast and the coalescence phenomenon. However, their insensitivity to lateral force, absence of long-range hydrophobic attraction, and the presence of possible contaminants and scratches on these domains suggested that these objects are most likely blisters formed by the stretched PS film. Furthermore, the analysis of the PS film before and after contact with water suggested that the film stretches and deforms after being exposed to water. The permeation of water at the PS–silicon interface, caused by osmosis or defects present on the film, can be a reasonable explanation for the nucleation of these spherical domains.
Keywords: AFM; blisters; contaminants; defects; nanobubbles; water permeation